The Problems of Kadazandusun Bumiputeraism: Promises, Privileges and Politics - James F. Ongkili (Kajian Malaysia, 2003)
There was a time in Kadazan history when association with the term bumiputera suggested an elevated status, a special position and even to some, a dignified rank. Such a time was the mid-sixties of newlyindependent Sabah, where Kadazans enchanted by the privileges of bumiputeraism were appreciative of the appellation "sons of the soil".